Marital Rape in Indonesia in Maqashid Shari’ah Perspective - Mutasir, Mutasir; Busyro, Wahyi (Jurnal Syariah dan Hukum Komparatif, 2023)
This article contains the concept of marital rape in Indonesian law, both positive law and Islamic law which is reviewed through maqashid shari’ah. Marital rape is included in the category of domestic violence that can happen to anyone. The type of research that will be used in this legal research is normative legal research. This research is a perspective legal research, which does not require hypotheses that must be proven, but provides perspective on what should be done. Analysis of the marital rape problem is carried out using the maqashid shari’ah approach where the applicable regulations regarding marital rape guarantee 5 main principles in Islam, namely maintaining religion, soul, reason, offspring and property maintained. The results of this study resulted in an understanding from the Qur’anic point of view regarding mu’asyarah bi al-ma’ruf and the maqashid shari’ah view on marital rape. So marital rape for any reason is strictly prohibited because it can damage the 5 main principles in Islam, namely maintaining religion, soul, reason, offspring and property and the law in force in Indonesia still does not provide special protection to victims. Although there is a hadith that shows that wives should not reject their husbands and can be categorized into nushuz, husbands are also required to come to their wives in a ma’ruf way and understand the wife’s condition so that there is no coercion that will hurt both physically and psychologically.